Prescribed opioid use is associated with increased all-purpose emergency department visits and hospitalizations in community-dwelling older adults in the United States - Ge, Song; Tian, Chong; Wu, Liang; Liu, Minhui; Lu, Haidong (Frontiers in Psychiatry, 2022)
Background The geriatric and health characteristics of older adults make them more susceptible to the effects of opioids than younger groups. The number of older adults in the United States visiting the emergency department (ED) and overusing opioids has increased in recent years. Research examining their relationship is, however, limited. Methods Using information from the 2020 National Health Interview Survey (NHIS), we included older adults aged 65 and older. To investigate the relationship between prescribed opioid use and 12-months ED visits and hospitalizations, linear regression and logistic regression models were built while adjusting for age, sex, ethnicity, education, employment, general health status, history of depression, and living arrangement. Results Our study population consisted of 8,631 participants (mean age 74.3). Most of them were females (58.3%) and Caucasian (81.6%). About 16% of the participants used prescribed opioids over the past 12 months. Of the participants with prescribed opioid use, 65.1% of them did so to treat chronic pain. The adjusted regression models revealed that prescribed opioid use was independently and positively associated with 12-months ED visits (β = 0.22, 95% confidence interval [CI] 0.18, 0.26) and hospitalizations (Odds ratio [OR] = 3.78, 95% CI 3.29, 4.35). Other risk factors for 12-months ED visits and/or hospitalizations included advanced age, male gender, unemployment/retirement, African American ethnicity, living alone, fair or poor general health status, and history of depression. Discussions Clinicians should screen older adults at high risk for ED visits and hospitalizations and explore multimodal pain management with them to help them reduce/stop using opioids. These efforts may decrease their chronic pain, opioid use, opioid use-related adverse health outcomes, ED visits, as well as hospitalizations.